2001
DOI: 10.1080/10789669.2001.10391429
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Charging Inlet Diffuser Performance in Stratified Chilled Water Storage Tanks with Radial Diffusers: Part 2–Dimensional Analysis, Parametric Simulations and Simplified Model Development

Abstract: A parametric study of the thermal performance during charging of a full-scale radial inlet diffuser in a cylindrical stratified chilled water storage tank was performed by applying factorial experimental theory to the results of simulations performed with a validated computational fluid dynamics (CFD) model. Part 1 describes the development and validation of the CFD model. Part 2 summarizes the results of the parametric study. Dimensional storage tank and inlet diffuser parameters having the potential to influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…They concluded that Re i is not of first-order importance for this diffuser type within typical full-scale tank operating parameter ranges that included Re i as large as 12,000. They also demonstrated that effects attributed to Re i could be explained to some extent by other parameters that are not represented in the current design methodology (Musser and Bahnfleth 2001b). The most significant parameters influencing radial diffuser performance were found to be Ri, R D /R W , and R D /h i , where Ri is the Richardson number, defined as in Equation 2, R D is the radius of the diffuser disk, and R W is the tank radius.…”
Section: Existing Diffuser Design Guidancementioning
confidence: 89%
“…They concluded that Re i is not of first-order importance for this diffuser type within typical full-scale tank operating parameter ranges that included Re i as large as 12,000. They also demonstrated that effects attributed to Re i could be explained to some extent by other parameters that are not represented in the current design methodology (Musser and Bahnfleth 2001b). The most significant parameters influencing radial diffuser performance were found to be Ri, R D /R W , and R D /h i , where Ri is the Richardson number, defined as in Equation 2, R D is the radius of the diffuser disk, and R W is the tank radius.…”
Section: Existing Diffuser Design Guidancementioning
confidence: 89%
“…Από τις κύριες κατηγορίες είναι η γεωμετρία της δεξαμενής. Μπορεί να είναι κυλινδρικής κατακόρυφου προσανατολισμού ( (Shin et al, 2004), (Musser and Bahnfleth, 2001), κ.α. ), κυλινδρικής οριζόντιου προσανατολισμού ( (Young and Baughn, 1981), (Helwa et al, 1995), (Consul et al, 2004), (Aviv et al, 2009)), ορθογωνικής (Nakos (1994), Chung et al (2008), Papanicolaou and Belessiotis (2009), κ.α.)…”
Section: 2unclassified